1977
DOI: 10.1056/nejm197711172972004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Favoring the Use of Anticoagulants in the Hospital Phase of Acute Myocardial Infarction

Abstract: Since the last comprehensive review of anticoagulation in acute myocardial infarction four additional randomized control trials have been reported. The overwhelming majority of all trials favored anticoagulation. Rates of thromboembolism were higher in the control, and hemorrhagic complications in the anticoagulated group. Pooling of all randomized control trials gives mean case fatality rates of 19.6% for the control and 15.4% for the anticoagulated group, a relative reduction of 21% (P less than 0.05 or less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(120 citation statements)
references
References 34 publications
2
117
0
1
Order By: Relevance
“…Reports have described the shortening of decision time by means of early recognition of symptoms by education of patients, 5 the 'chain of survival' concept advocated by the American Heart Association, 6 thrombolytic therapy, 7-13 anticoagulant therapy, 7,8,14,15 emergency PTCA, 13,[16][17][18][19][20][21][22][23] assisted circulation 24,25 and a system to determine the effect of prehospital-initiated treatment of myocardial infarction. 26,27 Many reports have shown that case-fatality rates of AMI patients arriving quickly at specialty institutions are decreased by recanalization therapy and assisted circulation in contrast to patients not so treated.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have described the shortening of decision time by means of early recognition of symptoms by education of patients, 5 the 'chain of survival' concept advocated by the American Heart Association, 6 thrombolytic therapy, 7-13 anticoagulant therapy, 7,8,14,15 emergency PTCA, 13,[16][17][18][19][20][21][22][23] assisted circulation 24,25 and a system to determine the effect of prehospital-initiated treatment of myocardial infarction. 26,27 Many reports have shown that case-fatality rates of AMI patients arriving quickly at specialty institutions are decreased by recanalization therapy and assisted circulation in contrast to patients not so treated.…”
Section: Discussionmentioning
confidence: 99%
“…Larger estimates of treatment effects have been shown in nonrandomized, compared with randomized, studies. 6,7 In addition to being randomly assigned, the allocation of study participants (that is, into which group a patient will be assigned) must be adequately concealed. The treating physician, participant, and anybody else associated with outcome assessment must be unaware of the randomization sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, all such observations suggest but are unable to establish the relative benefit of revascularization or the true value of the baseline test strategy to predict outcome with differing treatments. This limitation, the absence of a robust and appropriate control group, has led to false conclusions, later disproved with appropriate randomized trials, about the utility of a wide variety of clinical therapies, including surgery for Ménière's disease, 101 warfarin for acute myocardial infarction, 102 portosystemic shunts, 103 and antiarrhythmic therapy after myocardial infarction. 104 This is likely to be important for patients with renal artery hypertension.…”
Section: Limitations Of Nonrandomized Evidencementioning
confidence: 99%